Step
*
1
2
1
1
3
3
of Lemma
polymorphic-choice-base
1. f : ⋂A:Type. (A ⟶ A ⟶ A)
2. ∀x,y:Base.  (↓((f x y) = x ∈ Base) ∨ ((f x y) = y ∈ Base))
3. ∀z:Base. ((f z z) = z ∈ Base)
4. ((f 0 1) = 0 ∈ Base) ∨ ((f 0 1) = 1 ∈ Base)
5. ((f 0 1) = 0 ∈ Base) 
⇒ ((∀y:Base. ((f 1 y) = 1 ∈ Base)) ∧ (∀x:Base. ((f x 0) = x ∈ Base)))
6. ((f 0 1) = 1 ∈ Base) 
⇒ ((∀y:Base. ((f 1 y) = y ∈ Base)) ∧ (∀x:Base. ((f x 0) = 0 ∈ Base)))
⊢ (∀x,y:Base.  ((f x y) = x ∈ Base)) ∨ (∀x,y:Base.  ((f x y) = y ∈ Base))
BY
{ ((((D -3 THEN ThinTrivial)
    THENL [ Assert ⌜∀x,y:Base.  ((f x y) = x ∈ Base)⌝  Assert ⌜∀x,y:Base.  ((f x y) = y ∈ Base)⌝⋅])
   THENM (MoveToConcl (-1) THEN GenConcl ⌜f = F ∈ (Base ⟶ Base ⟶ Base)⌝⋅ THEN Auto)
   )
   THEN Auto
   ) }
1
1. f : ⋂A:Type. (A ⟶ A ⟶ A)
2. ∀x,y:Base.  (↓((f x y) = x ∈ Base) ∨ ((f x y) = y ∈ Base))
3. ∀z:Base. ((f z z) = z ∈ Base)
4. (f 0 1) = 0 ∈ Base
5. ((f 0 1) = 1 ∈ Base) 
⇒ ((∀y:Base. ((f 1 y) = y ∈ Base)) ∧ (∀x:Base. ((f x 0) = 0 ∈ Base)))
6. ∀y:Base. ((f 1 y) = 1 ∈ Base)
7. ∀x:Base. ((f x 0) = x ∈ Base)
8. x : Base
9. y : Base
⊢ (f x y) = x ∈ Base
2
1. f : ⋂A:Type. (A ⟶ A ⟶ A)
2. ∀x,y:Base.  (↓((f x y) = x ∈ Base) ∨ ((f x y) = y ∈ Base))
3. ∀z:Base. ((f z z) = z ∈ Base)
4. (f 0 1) = 1 ∈ Base
5. ((f 0 1) = 0 ∈ Base) 
⇒ ((∀y:Base. ((f 1 y) = 1 ∈ Base)) ∧ (∀x:Base. ((f x 0) = x ∈ Base)))
6. ∀y:Base. ((f 1 y) = y ∈ Base)
7. ∀x:Base. ((f x 0) = 0 ∈ Base)
8. x : Base
9. y : Base
⊢ (f x y) = y ∈ Base
Latex:
Latex:
1.  f  :  \mcap{}A:Type.  (A  {}\mrightarrow{}  A  {}\mrightarrow{}  A)
2.  \mforall{}x,y:Base.    (\mdownarrow{}((f  x  y)  =  x)  \mvee{}  ((f  x  y)  =  y))
3.  \mforall{}z:Base.  ((f  z  z)  =  z)
4.  ((f  0  1)  =  0)  \mvee{}  ((f  0  1)  =  1)
5.  ((f  0  1)  =  0)  {}\mRightarrow{}  ((\mforall{}y:Base.  ((f  1  y)  =  1))  \mwedge{}  (\mforall{}x:Base.  ((f  x  0)  =  x)))
6.  ((f  0  1)  =  1)  {}\mRightarrow{}  ((\mforall{}y:Base.  ((f  1  y)  =  y))  \mwedge{}  (\mforall{}x:Base.  ((f  x  0)  =  0)))
\mvdash{}  (\mforall{}x,y:Base.    ((f  x  y)  =  x))  \mvee{}  (\mforall{}x,y:Base.    ((f  x  y)  =  y))
By
Latex:
((((D  -3  THEN  ThinTrivial)
    THENL  [  Assert  \mkleeneopen{}\mforall{}x,y:Base.    ((f  x  y)  =  x)\mkleeneclose{}  ;  Assert  \mkleeneopen{}\mforall{}x,y:Base.    ((f  x  y)  =  y)\mkleeneclose{}\mcdot{}])
  THENM  (MoveToConcl  (-1)  THEN  GenConcl  \mkleeneopen{}f  =  F\mkleeneclose{}\mcdot{}  THEN  Auto)
  )
  THEN  Auto
  )
Home
Index